2018
DOI: 10.1016/j.jjcc.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of novel automated assessment of aortic annulus by intraoperative three-dimensional transesophageal echocardiography in patients with severe aortic stenosis: Comparison with conventional cross-sectional assessment

Abstract: For aortic annular measurements using 3D TEE in AS patients, semi-automated analysis using the novel automated software reduced analytical time while maintaining similar accuracy compared to the conventional cross-sectional analysis. This automated software may have acceptable feasibility in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…However, 3D TEE has been shown to be a viable alternative to MDCT due to its strong correlation and/or agreement with MDCT aortic annular measurements [18][19][20][21], attesting its reliability in clinical settings and, therefore, its usefulness in providing correct measurements of the aortic annulus prior to TAVI, which is in concordance with the results of our study. The 3D TEE technique can also offer important information about aortic root morphology [22], such as different transverse areas and longitudinal distances between tricuspid and bicuspid AS patients, the latter being larger, entailing different impacts on pressure recovery.…”
Section: Discussionsupporting
confidence: 90%
“…However, 3D TEE has been shown to be a viable alternative to MDCT due to its strong correlation and/or agreement with MDCT aortic annular measurements [18][19][20][21], attesting its reliability in clinical settings and, therefore, its usefulness in providing correct measurements of the aortic annulus prior to TAVI, which is in concordance with the results of our study. The 3D TEE technique can also offer important information about aortic root morphology [22], such as different transverse areas and longitudinal distances between tricuspid and bicuspid AS patients, the latter being larger, entailing different impacts on pressure recovery.…”
Section: Discussionsupporting
confidence: 90%
“…Their Bland-Altman analysis showed narrower 95% confidence interval with fewer data points outside this zone. 4 This could be related to a variety of factors such as variability in the distribution and severity of annular calcium in their population compared to the authors'. Including fewer patients with severe annular calcification, thus fewer patients with distorted annular geometry, would likely improve upon the observed accuracy of automated annular measurement.…”
Section: Discussionmentioning
confidence: 88%
“…The Bland-Altman plots showed 8 of 47 data points were outside of the 95% limits of agreement in the 2D dataset, whereas only 3 to 4 of 47 datapoints were outside of the 95% limits of agreement in the automated 3D data, suggesting more clinical reliability of automated 3D analysis. [3][4][5][6] Automated analysis is an area of active interest in the literature. Calleja et al described use of a previous version of this software to show automated measurements of the aortic root are feasible in normal, aortic stenosis, and aortic regurgitation patients and correlate to MDCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Automation of 3D TAVR sizing is an inevitable step as manufacturers look to encourage the use of TEE in the MDCT era. Several small studies have demonstrated feasibility and noninferiority although the optimal current model appears to be semi‐automated with a degree of operator control 28–30 . The technology provides a more efficient workflow and allows neighboring structures such as the mitral valve to be assessed in tandom (Figure 12).…”
Section: Specific Areas That Benefit From Real Time 3d Assessmentmentioning
confidence: 99%